2016
DOI: 10.1161/atvbaha.115.307032
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Cingulin Regulates Endothelial Barrier Function In Vitro and In Vivo

Abstract: Objective-Cingulin is a cytoplasmic component of tight junctions. Although modulation of cingulin levels in cultured epithelial model systems has no significant effect on barrier function, evidence from cingulin knockout mice suggests that cingulin may be involved in the regulation of the behavior of epithelial or endothelial cells. Here, we investigate the role of cingulin in the barrier function of endothelial cells. Approach and Results-We show that cingulin is expressed in human endothelial cells of the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 40 publications
4
53
0
Order By: Relevance
“…Cingulin overexpression in cultured ECs induced TJ formation and strengthened the endothelial barrier, although cingulin knock-out only minimally increased basal EC permeability to low molecular weight tracers, without affecting basal permeability to high molecular weight molecules (39). These results are consistent with our data showing no significant differences in basal macromolecular permeability between control and cingulin knockdown ECs.…”
Section: Discussionsupporting
confidence: 91%
“…Cingulin overexpression in cultured ECs induced TJ formation and strengthened the endothelial barrier, although cingulin knock-out only minimally increased basal EC permeability to low molecular weight tracers, without affecting basal permeability to high molecular weight molecules (39). These results are consistent with our data showing no significant differences in basal macromolecular permeability between control and cingulin knockdown ECs.…”
Section: Discussionsupporting
confidence: 91%
“…Via their cytoplasmic tail, these proteins are anchored to the peripheral actin cytoskeleton by a platform of scaffolding proteins including ZO‐1, cingulin and paracingulin (Fig. ) and interact with regulatory proteins such as Rho GTPases as well as kinases and phosphatases …”
Section: Structure Of the Endothelial Barriermentioning
confidence: 99%
“…In this context, ZO‐1 was shown to form a complex with JACOP (a cingulin‐like protein 1), which then serves as a platform for junctional recruitment of the RhoA activator p114RHoGEF to modulate junctional actomyosin contractility and thereby to stimulate the coupling of the mechano‐transducer vinculin to VE‐cadherin for maintenance of junctional integrity . However, another study showed that overexpression of cingulin (CGN), a protein similar to JACOP, increased barrier properties and this effect was accompanied by decreased claudin‐5 expression in vitro whereas in vivo (in CGN −/− mice) the expression of TJ proteins was unchanged …”
Section: Structure Of the Endothelial Barriermentioning
confidence: 99%
“…Cingulin is a component of endothelial tight junctions and serves to prevent formation of stress-induced membrane alterations. Overexpression of cingulin in cultured endothelial cells induced tight junction formation and improves endothelial barrier function[56]. A study in a rat lung transplantation model showed that intravascular administration of a cingulin-derived peptide during donor lung procurement, followed by intraperitoneal administration of the same peptide at the time of reperfusion reduced pulmonary edema and improved oxygenation up to 1 month after surgery [57].…”
Section: Experimental Evidence For New Targets For Prevention Of Pgdmentioning
confidence: 99%